2012
DOI: 10.3183/npprj-2012-27-02-p202-207
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical retention – Influence of filler floc size and grammage of the fibre web

Abstract: An investigation of the impact of particle size on the mechanical retention of particles in a fibre network has been conducted. The particles used were five sets of quartz particle fractions having fairly narrow particle size distributions with average particle size ranging from a few μm to around 100 μm. The particles were used to model flocculated filler aggregates as part of a larger study of the effect of pre-flocculation on mechanical retention. Pre-flocculation of the filler is a possible strategy to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In summary, we find from the sampled fibre-fines fraction a (1) depletion of fibre-fines outside the network, speculated to result from fibre-fines interaction with the fibre network, (2) a consequent accumulation of fibre-fines confined to the network interface, and (3) a homogenous distribution of fibre-fines at bulk concentration in the network core. The accumulation of fibres-fines at the network interface indicates a hindered fibre-fines transport through the network pores: fibre-fines may be caged and retained as in a filter that is formed by intersecting fibres [comparable to the mechanical retention argument of fines in formed fibre networks (Athley et al 2012)]. A consequence is, that the mobility of fibre-fines in the streaming network will depend on the network structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we find from the sampled fibre-fines fraction a (1) depletion of fibre-fines outside the network, speculated to result from fibre-fines interaction with the fibre network, (2) a consequent accumulation of fibre-fines confined to the network interface, and (3) a homogenous distribution of fibre-fines at bulk concentration in the network core. The accumulation of fibres-fines at the network interface indicates a hindered fibre-fines transport through the network pores: fibre-fines may be caged and retained as in a filter that is formed by intersecting fibres [comparable to the mechanical retention argument of fines in formed fibre networks (Athley et al 2012)]. A consequence is, that the mobility of fibre-fines in the streaming network will depend on the network structure.…”
Section: Resultsmentioning
confidence: 99%
“…Fines are retained in the established network, which was shown to be a size exclusion process, i.e. fines that are larger than the pore size of the formed network are retained (Athley et al 2012). The relative motion of fines in the network is hence a function of the fibrefines size and the fibre network's pore structure.…”
Section: Streaming Fibre Network and Fines Distributionmentioning
confidence: 99%
“…Several studies were found where FBRM was used to study the flocculation of fillers (e.g. Alfano et al 1998;Fuente et al 2003;Athley et al 2012;Björk et al 2012). Additionally, one study was found where FBRM was used to study the retention of inorganic microparticles for papermaking (Gerli et al 2000).…”
Section: Reflectance Methodsmentioning
confidence: 99%
“…Achieving a high solid content, that is, retention of filler in a paper sheet is critical in achieving ceramic components with mechanical stability 1 . Retention can be increased by various mechanisms, distinguishing between mechanical retention (hooking of the powder particles to the fibers) and chemical retention (coagulation and flocculation processes in the suspension, which increase the effective particle size) 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…wileyonlinelibrary.com/journal/jace 6755 can be increased by various mechanisms, distinguishing between mechanical retention (hooking of the powder particles to the fibers) and chemical retention (coagulation and flocculation processes in the suspension, which increase the effective particle size). 3,4 Although the paper-derived ceramic processing technique has been mainly used for high-temperature refractory ceramics, such as Al 2 O 3 , 5 SiC, 2 and Ti 3 SiC 2 , 6 it is also feasible to fabricate electro-active ceramic materials. 7 For example, Menge et al 7 demonstrated the fabrication of ferroelectric BaTiO 3 with acceptable functional properties using the paper-derived method.…”
Section: Introductionmentioning
confidence: 99%